PENGARUH MEDIA PEMBELAJARAN BERBASIS PODCAST TERHADAP KETERAMPILAN BERBICARA PADA SISWA MTs. Islamiyah GUPPI - Sri Muliatik (HIBRUL ULAMA, 2025)
This study aims to determine the effect of podcast-based learning media on junior high school students’ speaking skills. The research employed an experimental method with a pretest-posttest control group design. The subjects were divided into two groups: the experimental class, which used podcast media, and the control class, which applied conventional methods. The findings revealed that before the treatment, students’ speaking skills in both groups were relatively similar, with an average pretest score of 62.5 in the experimental class and 61.8 in the control class. After the treatment, the experimental class showed a significant improvement with an average posttest score of 80.3, while the control class only reached 70.1. The greatest improvement in the experimental class was observed in fluency and confidence, followed by vocabulary and pronunciation.The t-test results indicated a significant difference (p < 0.05) in all aspects of speaking skills between the experimental and control classes. Therefore, it can be concluded that podcast-based learning media has a positive and significant effect on improving junior high school students’ speaking skills.